EVALUASI LAHAN UBI BANGGAI MENGGUNAKAN KRITERIA KESESUAIAN UBI JALAR DI KECAMATAN TOTIKUM KABUPATEN BANGGAI KEPULAUAN - Zaenuddin, Ruslan A.; Nur Bi'a, Nur bia; Sariani, Sariani; Ladonu, Moh Ilham (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2024)
Banggai yam is one of the food crop agricultural commodities categorized as an endemic plant of Banggai Islands Regency. Besides being endemic, Banggai yam is also the main food for the people of Banggai Islands, especially in Totikum. So it is necessary to conduct research with the aim of knowing the nutrients in banggai yam land and the direction of banggai yam development in Sambiut village and Abason village, Totikum District, Banggai Islands Regency. The research was conducted in Sambiut and Abason Villages using a descriptive exploratory survey approach. Furthermore, the results of the analysis obtained will be tabulated in tabular form and narrated in sentence form. Based on the results of laboratory analysis of banggai yam plants in the totikum district of Sambiut and Abason villages have a marginal category (S3), because the limiting factor is rainfall base saturation. The limiting factor of rainfall can be improved by changing the planting time or making irrigation channels for the water needs of plants, although it requires relatively high costs. Furthermore, the limiting factor of base saturation can be improved by applying dolomite lime or organic materials such as biochar. Thus, the results of potential land suitability in Sambiut and Abason Villages are moderately suitable (S2). These results are expected to provide information to stakeholders in managing banggai yam land in order to obtain more production in the future, so that Ubi banggai can be available as food in a sustainable manner.